2017
DOI: 10.29312/remexca.v8i3.43
|View full text |Cite
|
Sign up to set email alerts
|

Envejecimiento acelerado y vigor de semillas del pasto Brachiaria brizantha cv Insurgente

Abstract: Con el objetivo de evaluar pruebas de vigor en semilla de Brachiaria brizantha cv. Insurgente, dos lotes de semilla, con diferente calidad física y fisiológica inicial, cosechados el 28 de septiembre (lote 1; otoño) y 21 de diciembre (lote 2; invierno) del mismo año, se sometieron a seis temperaturas (40, 41, 42, 43, 44 y 45 oC) y siete periodos (24, 36, 48, 60, 72, 84 y 96 h) de envejecimiento, a 100% de HR. Se utilizó un diseño completamente al azar, con arreglo factorial y cuatro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Tunes et al (2011) reported that a seed ageing test performed on 4 seed lots of L. multiflorum with an increased duration of 72 vs. 48 h reduced germination by an average of 38%. The recommended temperatures for the ageing test and the length of seed exposure vary by forage species: for Brachiaria brizantha, Hernández et al (2017) recommended 40 ºC during 48 or 60 h. For L. multiflorum, the recommended temperature is 41 ºC and exposure time 24, 48 or 72 h, depending on whether a traditional test or an alternative test with NaCl is performed (Tunes et al 2011). In F. pratensis the recommended temperature is 41 °C and exposure time 48 or 72 h (Stanisavljević et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Tunes et al (2011) reported that a seed ageing test performed on 4 seed lots of L. multiflorum with an increased duration of 72 vs. 48 h reduced germination by an average of 38%. The recommended temperatures for the ageing test and the length of seed exposure vary by forage species: for Brachiaria brizantha, Hernández et al (2017) recommended 40 ºC during 48 or 60 h. For L. multiflorum, the recommended temperature is 41 ºC and exposure time 24, 48 or 72 h, depending on whether a traditional test or an alternative test with NaCl is performed (Tunes et al 2011). In F. pratensis the recommended temperature is 41 °C and exposure time 48 or 72 h (Stanisavljević et al 2013).…”
Section: Methodsmentioning
confidence: 99%